The enterprise management in the force majeure conditions of its activities - Viktoriia Bozhanova; Valerii Vecherov; Oleksandra Kononova; Olena Chernysheva; Dmytro Dykun (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The latest spread of military conflicts globally became a prerequisite for choosing the goal of this scientific study: to develop recommendations for the use of an enterprise management tool under force majeure circumstances and of its activity and its approval. The scientific novelty was the proposal to use the tool of the theory of limitations of systems for the management of enterprises in force majeure conditions (war). The practical value is that the article proposes a universal management tool for any enterprise in force majeure conditions of operation, in which any enterprises of any countries may find themselves as a result of military aggression by invaders. In the scientific article, using the example of VUD LLC (Dnipro, Ukraine), which produces small-scale concrete products, economic indicators were analyzed, corresponding graphs were constructed, conclusions were drawn. These made it possible to find a “bottleneck” according to the theory of system limitations and develop practical recommendations for solving his problems in force majeure conditions of the organization’s activity. Therefore, the research carried out regarding the work of this enterprise during the war in Ukraine made it possible to expose such weak points and develop new opportunities and potential for development, which will make this enterprise more competitive. The management tool of operational management – the theory of system limitations provides entrepreneurs with a universal approach to finding problems arising in force majeure conditions. Therefore, the sequence of management actions by enterprises should be aimed at finding the “bottlenecks” and making efforts to expand them in any of its subsystems.